The study of biodegradable thermoplastics sago starch - Ahmad, Zuraida; Anuar, Hazleen; Yusof, Yusliza (Trans Tech Publications, Switzerland, 2011)
The motivation of this work is to lessen the dependence on non-degradable plastic packaging which can lead to waste disposal problems. In this paper, the alternative biodegradable material developed by using local available sago starch in the present of biodegradable glycerol as plasticizer, as well as a set of composition added with citric acid as co-plasticizer is reported. Starch was added with 15-30 w/w% of glycerol to prepare workable bioplastics. The samples were characterized by Thermal Gravimetric Analysis (TGA), Fourier Transform Infrared (FTIR) and tested for mechanical properties. The results reveale that, the tensile strength of the bioplastic is increasing with the increasing of glycerol until the optimum amount of 30 w/w%. The similar trend is also observed upon the addition of the citric acid. The decrease of the strength after the optimum point, however is obvious in the specimens with the addition of citric acid which is about 50% lower than the specimen without citric acid.